TECHNOLOGIES FOR DEVELOPING MANAGEMENT COMPETENCIES OF “SCHOOL ADVISORS” IN SECONDARY SCHOOLS OF UZBEKISTAN - Kazakova Saxiba Abdurayimovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article analyzes the scientific and methodological foundations for developing the managerial competencies of school counselors working in general education schools. The school counselor institute performs complex tasks such as coordinating socio-pedagogical processes, supporting student initiatives, analyzing behavioral and socio-skills development based on indicator monitoring, and managing neighborhood-school-family cooperation. Therefore, its professional training should be organized based on the competency approach, andragogic principles, pedagogical leadership, and knowledge-based management concepts. The article proposes an integrated model of a school counselor that includes strategic, analytical, project, communicative, and leadership competencies. This model is enriched with mechanisms for implementing it in practice through modular training, mentoring and coaching, action research, 360° assessment, and digital monitoring platforms. The research results substantiate that the systematic and gradual development of management competencies serves to increase the efficiency of internal school management and strengthen the socio-initiative potential of students.